Pellets comprising axial core and polymer sheath, and manufacture thereof

By using a granular structure combining axial filament cores and filler particles in fiber-reinforced plastic products, the problem of balancing density and stiffness in existing technologies is solved, achieving lightweight and high-strength fiber reinforcement.

CN119305054APending Publication Date: 2025-01-14SABIC GLOBAL TECHNOLOGIES BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411426914.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-12-15
Filing Date
2017-12-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, fiber-reinforced plastic products are difficult to reduce density while maintaining good rigidity, especially in injection molding methods with high glass fiber content, where density increases.

Method used

It adopts a granular structure containing an axial filament core and a polymer sheath, wherein the polymer sheath contains filler particles, the filament content accounts for 30-50% of the total weight, and a combination of glass bubbles and nano-clay particles is used as filler to reduce density while maintaining or increasing stiffness.

Benefits of technology

It achieves the goal of maintaining or improving the stiffness and strength of fiber-reinforced products while reducing density, making it suitable for various structural applications such as motor vehicle parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082423150000251
    Figure BDA0005082423150000251
  • Figure BDA0005082423150000281
    Figure BDA0005082423150000281
  • Figure BDA0005082423150000291
    Figure BDA0005082423150000291
Patent Text Reader

Abstract

A pellet having an axial direction and comprising a core extending in the axial direction and further comprising a polymeric sheath applied around the core, wherein the core comprises a plurality of filaments extending in the axial direction; the polymeric sheath is at least substantially free of the filaments; the polymer sheath comprises a plurality of filler particles; the pellets comprise filaments of at least 30% by weight, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50%, based on the total weight of the pellets. Further disclosed are reinforced articles obtained by molding a plurality of the pellets, as well as methods of making such pellets.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese patent application with application number 201780086329.6, application date December 14, 2017, and invention name “granules comprising an axial core and a polymer sheath, and their manufacture”.

[0002] The invention relates to a method for producing granules, reinforced articles and to a method for producing granules.

[0003] The fiber-reinforced plastics introduced more than half a century ago are composite materials with wide range of applications in industry, for example, in aerospace, automobile, chip, building and structural industries. The enhanced product can comprise any combination of individual materials, for example, a thermoplastic polymer (matrix) having dispersed fiber (reinforcement fiber) therein. Various organic fibers and inorganic fibers (such as glass fiber and carbon fiber) comprising synthetic fibers (such as polyamide, polytetrafluoroethylene, polyester), natural fibers (such as cotton, hemp, flax, jute) are often used as reinforcing fibers in composite materials.

[0004] The plastics industry has been using glass fibers in different forms for reinforcing polymer matrices to produce a variety of products. Glass fibers are usually supplied as multiple continuous very long filaments and can be in the form of strands or bundles, rovings or yarns. A filament is a single fiber of a reinforcing material. A bundle is a plurality of bundled filaments. A yarn is a collection of filaments or strands twisted together. A roving refers to a collection of bundles / strands wound into a package.

[0005] A method for producing a reinforced composition is described, for example, in WO 2009 / 080281. In this disclosure, a method for producing a long glass fiber reinforced thermoplastic polymer composition is described, the method comprising the following subsequent steps:

[0006] a. unwinding at least one continuous glass multifilament strand containing a sizing composition from a packaging material;

[0007] b. applying an impregnating agent to the at least one continuous glass multifilament strand to form an impregnated continuous multifilament strand;

[0008] c. applying a thermoplastic polymer sheath around the impregnated continuous multifilament strand to form a sheathed continuous multifilament strand; and

[0009] d. Cutting the jacketed continuous multifilament strands into pellets.

[0010] The pellets obtained with the method described above contain multifilament glass (strands) having the same length as the pellets. When these pellets are molded into articles, the stiffness of the articles is not sufficient for all applications. The stiffness of the articles can be improved by increasing the amount of glass fibers in the articles. However, pellets containing glass fibers in an amount higher than 50 wt.% are difficult to use in injection molding processes. In addition, with increasing glass fiber content, the density of the final part will increase, which is not always desirable, particularly in the automotive industry.

[0011] The international application WO 2016 / 062569 A1 of the present applicant relates to a method for conveying pellets of a glass fiber reinforced thermoplastic polymer composition from a loading position to an unloading position.

[0012] International application WO 206 / 091686 A1 of the present applicant relates to a process for producing a long glass fiber reinforced polypropylene composition containing from 10 to 70 wt. % of glass fibers, based on the weight of the composition.

[0013] It is an object of the present invention to provide a pellet for use in a method for preparing a reinforced article having a reduced density while maintaining good stiffness. In other words, it is an object of the present invention to increase the stiffness of an article while maintaining the same density or to reduce the weight of an article and maintain similar stiffness. One or more of these objects are achieved by the present invention as discussed in the appended claims. Summary of the invention

[0014] In a first aspect, the present invention relates to a granulate having an axial direction; the granulate comprises a core extending in the axial direction and comprises a polymer sheath having been applied around the core, wherein the core comprises a plurality of filaments, preferably glass filaments, extending in the axial direction; wherein the polymer sheath is at least substantially free of the (glass) filaments and wherein the polymer sheath comprises a plurality of filler particles; wherein the granulate comprises at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of (glass) filaments based on the total weight of the granulate.

[0015] In a second aspect, the present invention relates to a solid object obtained by moulding a plurality of granules according to the invention.

[0016] In a third aspect, the present invention relates to a method for preparing a pellet, the method comprising the steps of:

[0017] i) unwinding a plurality of continuous (glass) filaments from a packaging;

[0018] ii) optionally, applying an impregnation composition to the plurality of (glass) filaments to form an impregnated plurality of (glass) filaments;

[0019] iii) providing a polymer composition comprising at least one polymer and a plurality of filler particles;

[0020] iv) applying a polymer sheath comprising filler particles around the plurality of (glass) filaments to form a sheathed bundle comprising a core comprising the plurality of (glass) filaments and comprising a sheath comprising the polymer and filler particles: and

[0021] v) cutting the sheathed bundle into individual pellets, the individual pellets comprising a core extending in an axial direction and comprising a polymer sheath having been applied around the core, wherein the polymer sheath is at least substantially free of the (glass) filaments and wherein the polymer sheath comprises a plurality of filler particles; wherein the pellets comprise at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of (glass) filaments based on the total weight of the pellets.

[0022] definition

[0023] In this specification, a composite material means: comprising at least two separate materials. The granulate according to the present invention may be regarded as a composite granulate.

[0024] In this specification, pellets mean: round or tubular solid objects such as compressed blocks of matter.

[0025] In this specification, glass bubbles mean: hollow glass microspheres consisting of glass walls and internal voids. However, the plurality of glass bubbles may contain up to 20 wt.%, preferably up to 15 wt.%, more preferably up to 10 wt.% of solid glass particles by volume.

[0026] In this specification, filament means: a thin line or thread-like object or fiber.

[0027] In this specification, glass filaments mean: filaments made of glass.

[0028] In the present specification, multifilament means: a plurality of filaments, for example in the form of strands or bundles.

[0029] In this specification, a bundle means: a plurality of filaments fixed together or stacked together.

[0030] In this specification, clay means: granular silicate mineral material; natural product.

[0031] In this specification, nanoclay means: nanoparticles of clay; ie nanoparticles of (layered) mineral silicates.

[0032] In this specification, sepiolite clay means a specific type of clay that is a complex magnesium silicate, the typical chemical formula for which is Mg4Si6O 15 (OH). DETAILED DESCRIPTION

[0033] As discussed above, in a first aspect, the present invention relates to a pellet having an axial direction; the pellet comprises a core extending in the axial direction and comprises a polymer sheath having been applied around the core, wherein: * the core comprises a plurality of (glass) filaments extending in the axial direction; * the polymer sheath is at least substantially free of the filaments; * the polymer sheath comprises a plurality of filler particles; * the pellet comprises at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of filaments based on the total weight of the pellet. In other words, it relates to a pellet comprising a glass filament core surrounded by a filler-containing polymer sheath. This pellet can be used to prepare a reinforced article. The filler has a positive effect on the strength / stiffness of the reinforced article. The filler is preferably a low-weight filler that reduces the weight of the reinforced article while maintaining the same strength / stiffness or improving these.

[0034] In an embodiment, the present invention relates to a granular material having an axial direction; the granular material consists of a core extending in the axial direction and a polymer sheath having been applied around the core, wherein: * the core consists of a plurality of (impregnated) (glass) filaments extending in the axial direction; * the polymer sheath is at least substantially free of the filaments; * the polymer sheath comprises a plurality of filler particles; * the granular material comprises at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50%, by weight of filaments based on the total weight of the granular material.

[0035] The pellets according to the invention have at least two fillers, a first filler being filaments forming the core of the pellet and a second filler being filler particles present in a polymer sheath.

[0036] The pellets contain at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% of the filaments by weight of the core, based on the total weight of the pellets. This allows for sufficient strength in the reinforced articles prepared from the pellets. It is known that by increasing the amount of glass filaments in the core, the strength will increase with the weight of the pellets.

[0037] It has been unexpectedly discovered that the ratio of tensile modulus to density of fiber reinforced thermoplastic resin pellets can be significantly reduced by filling the polymer sheath with a particulate filler (e.g., hollow glass bubbles or microspheres or by nanoclays or combinations thereof); without substantially significantly reducing the tensile strength and other physical properties of the pellets. Thus, (glass) fiber filament reinforced thermoplastic pellets can be made in a lighter yet desirably strong form. The present invention can be used to make composite materials for use in various structural applications, such as, for example, parts for use in motor vehicles.

[0038] The pellets used in the present invention have a generally cylindrical shape having an axial length, i.e., a length in a direction perpendicular to the cross section of the cylinder. The core of the pellets has a generally cylindrical shape and comprises a multifilament (bundle) made of (glass) fibers optionally impregnated with an impregnating agent. The fibers have a length substantially equal to the axial length of the pellets. The core of the pellets is surrounded by a sheath having a generally tubular shape comprising a thermoplastic polymer and a filler around its circumference.

[0039] For the avoidance of doubt, it is understood that the pellets have a core sheath structure, wherein the core comprises an optional impregnant and glass multifilaments. The sheath is composed of a thermoplastic material comprising a filler and surrounds the core. The core (glass filaments) is substantially free of the material of the sheath. And the sheath is substantially free of filaments. Such pellet structures are obtainable by wire coating processes such as disclosed in WO 2009 / 080281 and are different from pellet structures obtained via typical pultrusion type processes such as disclosed in US 6,291,064.

[0040] In an embodiment of the first aspect, the filler particles present in the polymer sheath are glass bubbles preferably having an average diameter of between 10 and 30 microns, preferably between 15 and 25 microns. These glass bubbles are discussed in more detail below.

[0041] In an embodiment of the first aspect, the filler particles present in the polymer sheath are clay particles, preferably nanoclay particles, preferably sepiolite clay. These nanoclay particles are discussed in more detail below. In an embodiment of the first aspect, the filler particles present in the polymer sheath are a combination of glass bubbles and nanoclay particles. In an embodiment of the first aspect, the pellet contains between 3 and 20 wt.%, preferably between 5 and 10 wt.%, of the filler particles in the polymer sheath, based on the total weight of the pellet.

[0042] In embodiments where a combination of glass bubbles and nanoclay particles is used, this percentage relates to the combination of both filler particles.In an embodiment of the first aspect, the weight ratio between glass bubbles and nanoclay particles is between 0.5 and 2.0.

[0043] In an embodiment of the first aspect, the plurality of filaments are continuous multifilament glass. In an embodiment of the first aspect, the plurality of filaments preferably comprises from 2000 to 5000 filaments. In an embodiment of the first aspect, the filaments preferably each independently have a diameter from 5 to 50 microns, more preferably from 10 to 30 microns and most preferably from 15 to 25 microns. Preferably, the filaments each have substantially the same diameter, for example wherein at least 90% of all filaments forming the multifilament have a diameter within the range of +10% and -10% of the average diameter. In an embodiment of the first aspect, the filaments preferably have an average diameter (the mathematical mean of all filaments) from 5 to 50 microns, more preferably from 10 to 30 microns and most preferably from 15 to 25 microns.

[0044] In an embodiment of the first aspect, the polymer sheath is made of a polyolefin material, preferably polypropylene, more preferably polypropylene homopolymer, more preferably having a melt flow index (MFI) of at least 20 g / 10 min and / or having an MFI of at most 150 g / 10 min, most preferably in the range of 30 g / 10 min to 80 g / 10 min.

[0045] In an embodiment of the first aspect, the amount of polymer in the pellet is between 40 wt.% and 80 wt.% based on the total weight of the pellet. In an embodiment of the first aspect, the exposed ratio (the number of filaments observed (visually) on the cut edge of the pellet divided by the total number of filaments multiplied by 100%) is at least 95%. In an embodiment of the first aspect, the filler particles are glass bubbles and the glass bubble rupture is at most 30%, preferably at most 23%. In an embodiment of the first aspect, the polymer sheath comprises less than 5 wt.% of filaments, preferably less than 2 wt.% of filaments based on the total weight of the polymer sheath. This means substantially free of filaments.

[0046] In an embodiment of the first aspect, the core constitutes between 35% and 60% of the cross-sectional area of ​​the pellet and wherein the sheath constitutes between 40% and 65% of the cross-sectional area of ​​the pellet. To determine this, the cross-sectional area of ​​the pellet is determined and the cross-sectional area of ​​the filament core is determined separately. The difference between the two values ​​is the cross-sectional area of ​​the polymer sheath.

[0047] Preferably, the longitudinal variation of the radius of the core over the length of the pellet is between -5% and +5%, based on the average radius. Preferably, the variation of the radius of the core from one individual pellet to another is between -5% and +5%, based on the average radius. When the radius of the core is disclosed in this specification, unless otherwise stated, this means the average radius over the length as well as the average radius over several individual pellets.

[0048] Preferably, the longitudinal variation of the diameter of the pellets over the length of the pellets is between -5% and +5%, based on the average diameter. Preferably, the variation of the diameter of the core from one individual pellet to another is between -5% and +5%, based on the average diameter. When the diameter of a pellet is disclosed in this specification, unless otherwise stated, the average diameter over the length as well as the average diameter over several individual pellets is meant. Without wishing to be bound by any particular theory, the inventors of the present invention assume that due to the cutting step in producing the pellets, the diameter and shape of one or both ends of the pellets may show variation relative to the center of the pellet.

[0049] In an embodiment of the first aspect, the radius of the core is between 800 and 4000 microns and wherein the thickness of the sheath is between 500 and 1500 microns.

[0050] It should be noted that, when during the manufacturing process of preparing the pellets of the present invention, up to 2% of all pellets formed have an incompletely closed polymer sheath, which results in pellets with exposed filaments in the axial length - this is known as the zebra effect. It is not necessary to separate these zebra pellets from pellets with a completely closed polymer sheath, although these zebra pellets are not pellets according to the present invention.

[0051] In an embodiment of the second aspect, the fiber filaments reinforced object formed from the pellets of the present invention has an isotropic modulus of at least 5000 MPA, preferably at least 5500 MPA, and more preferably at least 6000 MPA. In an embodiment of the second aspect, the fiber filaments reinforced object formed from the pellets of the present invention has an effective modulus of at least 3.5 (m / s) 2 and 7(m / s) 2 Between, preferably 4 (m / s) 2 Up to 6 (m / s) 2 , more preferably 4.5 (m / s) 2 Up to 5.5 (m / s) 2 In an embodiment of the second aspect, the fiber filament reinforced object formed from the granules of the present invention has a density of at most 1.3, preferably 1.28, more preferably 1.25.

[0052] In an embodiment of the third aspect, during the process of producing the pellets of the present invention, the mixture of polymer and filler particles is applied to the plurality of filaments by a wire coating process as discussed above.

[0053] Filament

[0054] Multifilament bundles, preferably glass multifilament bundles, and their preparation are known in the art. The fibers in the bundle, preferably glass fibers, can be formed by any method known to those skilled in the art. Preferably, the fibers can be formed by a melt spinning process. The length of the fibers in the bundle is determined by the length of the pellets and can vary over a wide range. For example, the average length of the filaments in the pellets can vary between 10 mm and 50 mm, preferably between 10 mm-25 mm, and more preferably between 10 mm-20 mm. Due to the mechanical forces during the production of the object causing the breakage of the filaments, the average length of the filaments in the object formed from the pellets is less than the average length of the filaments in the pellets.

[0055] The fiber density of the fiber in the bundle can vary over a wide range. Preferably, the bundle can have from 500 to 10000 fibers / bundle and more preferably from 2000 to 5000 fibers / bundle. The diameter of the fiber in the bundle can vary widely. Preferably, the diameter range of the fiber in the bundle is from 5 to 50 microns, more preferably from 10 to 30 microns and most preferably from 15 microns to 25 microns. The fiber diameter outside these ranges tends to cause a reduction in mechanical properties and / or an increase in the wear of the equipment used. The diameter of the multifilament bundle in the pellet can be, for example, between 1mm and 7mm.

[0056] The multifilament bundle may include a sizing composition. Suitable examples of conventional sizing compositions include compositions based on solvents (such as organic materials dissolved in aqueous solution or dispersed in water) and compositions based on melting or radiation curing. More preferably, not only the aqueous sizing composition is applied to the individual fibers, but also an oil-based sizing composition may be applied. As described in the art, for example, in documents EP 1460166 A1, EP 0206189 A1 or US 4338233, the aqueous sizing composition typically includes a film former, a coupling agent and other additional components. The film former is usually present in an effective amount to protect the fiber from wear between the filaments and to provide integrity and processability of the fiber bundle after the fiber bundle is dried. Suitable examples of film formers generally include polyurethanes, polyesters (such as polycaprolactone), polyolefins (such as polypropylene), polyamides. It has been recognized in the art that the film former should be miscible with the polymer to be enhanced. For example, polycaprolactone can be used as a film former when nylon is used as the polymer to be reinforced; for reinforced polypropylene, suitable film formers typically include polyolefin waxes.

[0057] Coupling agents (in the sizing composition) are generally used to improve the adhesion between the matrix thermoplastic polymer and the fiber reinforcement. Suitable examples of coupling agents for fibers known in the art include organofunctional silanes. More preferably, the coupling agent added to the sizing composition is an aminosilane, such as aminomethyl-trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl-trimethoxysilane, γ-aminopropyl-trimethoxysilane, γ-methylaminopropyl-trimethoxysilane, δ-aminobutyl-triethoxysilane, 1,4-aminophenyl-trimethoxysilane. In a preferred embodiment of the method of the present invention, the fiber with the sizing composition containing aminosilane is applied as a multifilament bundle to produce good adhesion to the matrix formed by the molten thermoplastic polymer of the sheath. Any other additional components known to the technician may be present in the sizing composition. Suitable examples include lubricants, antistatic agents, crosslinking agents, plasticizers, surfactants, nucleating agents, antioxidants, pigments, and any combination thereof for preventing damage to the bundle by wear. The application of a size composition to formed filaments is well known in the art.

[0058] Typically, after applying the size composition on the fibers, the fibers are bundled into bundles and then wound onto bobbins to form packages. Multifilament bundles containing up to 2 wt.% of the size composition based on the total weight of the fibers in the multifilament bundle are preferably used in the pellets used in the process of the present invention. The amount of the size composition can be determined by loss on ignition (LOI). LOI is a well-known technique for determining the amount of size on a fiber. More preferably, multifilament bundles containing from 0.1 to 1 wt.% of the size composition as determined by loss on ignition (LOI) are used.

[0059] Preferably, one or more strands comprising (glass) fibers to which a size composition has been applied as an aqueous dispersant are used in the granules according to the invention. The size is generally a solvent-based material applied to the surface of the fibers to improve the fiber production process; preferably more than 90% of the size composition is solvent, which will be removed during drying.

[0060] Impregnation agent

[0061] The impregnating agent is generally a low molecular weight material that acts primarily as a lubricant and remains in the product during the entire process. The impregnating agent that can be used in the method according to the invention comprises at least one compound that is compatible with the thermoplastic polymer. The impregnating agent enables the dispersion of the fibers in the thermoplastic polymer matrix to be enhanced during the molding process.

[0062] The application temperature is selected so as to obtain the desired viscosity range. For example, when the substrate is polypropylene, the application temperature of the impregnating agent may be from 15°C to 200°C.

[0063] The amount of impregnating agent applied to the multifilament bundle containing the fibers depends on the thermoplastic matrix, the size (diameter) and concentration of the fibers forming the bundle, and the type of sizing agent on the surface of the fibers. The pellets according to the present invention may contain 1-10 wt.% impregnating agent based on the weight of the fibers in the multifilament bundle of the pellets. The weight ratio between glass and impregnating agent is between 4 and 40, preferably 5 to 25 and most preferably 8 to 20, based on the weight of the fibers in the multifilament bundle of the pellets. The impregnating agent helps the fibers to be evenly dispersed in the thermoplastic polymer matrix during molding, but the amount should not be too high because excess impregnating agent may adversely affect other properties of the product. It was found that the lower the viscosity, the less impregnating agent can be applied. For example, in the case where the thermoplastic matrix is ​​a polypropylene homopolymer having a melt index (MFI) (230°C / 2.16kg) of 25 to 65 g / 10 min and the reinforcing filaments have a diameter of 19 microns, the impregnating agent is preferably applied to the multifilament bundle in an amount of from 2 to 10 wt. %. The amount of the impregnating agent is preferably 0.05-6 wt. % based on the total weight of the pellets.

[0064] The impregnating agent should be compatible with the thermoplastic polymer to be enhanced, and can even be soluble in the polymer. The technician can select a suitable combination based on common sense, and such combinations can also be found in the art. Suitable examples of impregnating agents include compounds of low molar mass, such as low molar mass or oligomeric polyurethanes, polyesters (such as unsaturated polyesters, polycaprolactones, polyethylene terephthalate), poly (alpha-olefins) (such as branched polyethylene and polypropylene), polyamides (such as nylons), and other hydrocarbon resins. As a general rule, polar thermoplastic polymer matrices need to use impregnating agents containing polar functional groups; non-polar polymer matrices involve the use of impregnating agents with non-polar characteristics. For example, for enhanced polyamide or polyester, the impregnating agent can include low molecular weight polyurethane or polyester (like polycaprolactone). For enhanced polypropylene, the impregnating agent can include branched poly (alpha-olefins) (such as polyethylene wax, modified low molecular weight polypropylene), mineral oils (such as paraffin or silicon) and any mixture of these compounds. Preferably, the impregnating agent comprises a low molecular weight hydrocarbon compound (comprising, for example, a branched poly(α-olefin)) and more preferably, the impregnating agent comprises at least 70 wt.%, or at least 80 wt.% or even 90 wt.% of a branched polyethylene wax. In the case where the thermoplastic polymer is polypropylene, the wax is optionally mixed with, for example, from 10 wt.% to 80 wt.%, preferably 20 wt.%-70 wt.% of a hydrocarbon oil or wax, like paraffin oil, to achieve the desired viscosity level.

[0065] The impregnating agent is non-volatile and is substantially solvent-free. Non-volatile means that the impregnating agent does not evaporate under the processing conditions of application and application; i.e. it has a boiling point or range higher than the processing temperature. In the context of the present application, "substantially solvent-free" means that the impregnating agent contains less than 10% by mass of solvent, preferably less than 5% by mass of solvent. Most preferably, the impregnating agent does not contain any organic solvent.

[0066] The impregnating agent may be further mixed with other additives known in the art. Suitable examples include lubricants; antistatic agents; UV stabilizers; plasticizers; surfactants; nucleating agents; antioxidants; pigments; dyes; and adhesion promoters, such as modified polypropylene with maleated reactive groups; and any combination thereof, provided that the viscosity remains within the desired range.

[0067] Glass Bubble.

[0068] Many known hollow microspheres or bubbles can be used, typically glass is preferred. To improve the survivability of the bubbles during processing of the pellets to achieve the desired density reduction, it is typically preferred to use high strength glass bubbles. In some examples, the majority (e.g., more than 80%, preferably more than 90%, or even more than 95% or 99%) of the bubbles should exhibit a crush strength of at least 3,000 PSI, preferably greater than 10,000 PSI to withstand thermoplastic mixing and extrusion operations. In some embodiments, glass bubbles will preferably exhibit high survivability when exposed to a crush strength of at least 18,000 PSI to withstand palletizing and injection molding and mixing and extrusion operations.

[0069] The strength of glass bubbles is typically measured using ASTM D3102-72; "Hydrodynamic Collapse Strength of Hollow Glass Microspheres". An illustrative example of such glass bubbles is 3M TM Scotchlite TM S60HS glass bubbles, which are soda-lime borosilicate glass and exhibit an isocrushing strength of 18,000 psi, a density of 0.60 g / cc, and an average diameter of about 30 microns.

[0070] Preferably, the glass bubbles (e.g., more than 80%, preferably more than 90%, or even more than 95% or 99% of the glass bubbles) are hollow, thin-walled single-cell spheres. Preferably, the glass bubbles are borosilicate glass. The density of the glass bubbles (the density being the average density of a plurality of glass bubbles) may vary and may be, for example, between 0.4 g / cm 3 With 0.7g / cm 3 between.

[0071] Glass bubbles suitable for the present invention preferably have a g / cm 3and 0.90g / cm 3 Between, preferably between 0.40g / cm 3 With 0.70g / cm 3 The glass bubbles preferably have a density of between 100 and 200 psi. The glass bubbles preferably have a borosilicate glass. The glass bubbles preferably have an average particle size of between 12 and 30 microns, preferably between 15 and 25 microns. The glass bubbles preferably have an isostatic pressure resistance of between 100 MPa and 200 MPa. The glass bubbles preferably have a strength of 15,000 psi to 40,000 psi. The glass bubbles preferably have an average wall thickness of between 0.60 and 0.8 microns.

[0072] In glass bubbles (a commercially available example is 3M iM16K glass bubbles) with a mass of 0.46 g / cm 3 In the first embodiment of borosilicate glass, they have an average particle size of 20 microns; an isostatic pressure resistance of 113 MPa; they have a strength of 16500 psi, an average wall thickness of 0.72 microns, 18% glass and 82% gas (voids). The particle size distribution is as follows: 10% less than 13 microns; 50% less than 22 microns; and 90% less than 31 microns and the largest particle is 37 microns.

[0073] In glass bubbles (commercially available example is 3M iM30K glass bubbles) with a g / cm 3 In a second embodiment of a borosilicate glass having a density of 10000 psi and being a borosilicate glass, they have an average particle size of 16 microns; an isostatic pressure resistance of 193 MPa; they have a strength of 30,000 psi, an average wall thickness of 0.70 microns, 24% glass and 76% gas (voids). The particle size distribution is as follows: 10% less than 9 microns; 50% less than 16 microns; and 90% less than 25 microns and the largest particle is 29 microns.

[0074] The glass bubbles according to the present invention may have an outer coating.The glass bubbles according to the present invention may have a modified surface, preferably wherein the surface is modified with an organic material, such as aminosilane.

[0075] In composite materials, hollow glass microspheres are generally stronger and stiffer than the surrounding polymer matrix; this combination gives the material (e.g., a polymer sheath comprising a polymer and a second filler) its designed properties. In an embodiment, the polymer sheath (matrix) comprises hollow glass microspheres in some ordered and / or high-density pattern. In an embodiment, a plurality of hollow glass microspheres are dispersed throughout the matrix material so that they are not in contact, in other words, the outside of the glass bubbles is covered by the matrix material. In this way, the polymer matrix therefore helps to distribute any applied load or stress among the hollow glass microspheres. In order to improve the mixing and filling of the hollow glass microspheres throughout the polymer matrix, the surface modification of the hollow glass microspheres can be performed using chemical agents. Such surface modifications can help to overcome the forces that prevent the polymer matrix from forming a substantially continuous phase of the material. Good mixing and optionally combining of the optionally surface-treated microspheres allows the material properties to be adjusted, but careful processing and manufacturing are also features that have an impact on the material properties. The surface chemical agent is preferably an organic material; this material can provide an external coating on the microparticles that promotes close bonding of the polymer and the microparticles. Preferred amounts of surface modifiers are from about 0.005 wt.% to 8 wt.%, or from about 0.02 wt.% to 3 wt.%.

[0076] The hollow glass spheres are strong enough to avoid being crushed or broken during further processing of the polymer compound, such as by high pressure spraying, kneading, extrusion or injection molding. In some embodiments, the microspheres have a density similar to the density of the polymer sheath into which they are introduced; this has the effect that they are evenly distributed within the polymer after introduction and mixing.

[0077] The glass bubbles used in the present invention can be both hollow glass spheres and solid glass spheres, which are commercially available; most commercial-grade hollow glass spheres contain a certain percentage (preferably less than 10 wt.%) of solid glass spheres that are not separated out before use. Preferably, the glass bubbles do not show significant expansion after heating.

[0078] Nano clay particles

[0079] In an embodiment of the first aspect, the nanoclay particles preferably have a ratio between length and diameter of between 1 and 1000, more preferably between 10 and 800.

[0080] In an embodiment of the first aspect, the nanoclay particles preferably have a length between 0.1 and 10 microns, preferably 0.4 and 5 microns.

[0081] Fillers

[0082] In the method according to the present invention, fillers can be used. Fillers can preferably have any profile, such as ball, plate, fiber, needle-like, sheet-like, whisker or irregularly shaped particulate fillers. Suitable fillers typically have an average longest diameter of about 1 nanometer to about 500 microns, especially about 10 nanometers to about 100 microns. The average aspect ratio (length: diameter) of some fibrous, needle-like or whisker-shaped fillers (such as glass or wollastonite) can be about 1.5 to about 1000, although longer fibers are also within the scope of the present invention. The average aspect ratio (average diameter of circles of equal area: average thickness) of plate-like fillers (such as mica, talcum or kaolin) can be greater than about 5, especially about 10 to about 1000, more particularly about 10 to about 200. Bimodal, trimodal or higher aspect ratio mixtures can also be used.

[0083] Fillers having spheres, plates, needles, flakes or irregular shapes preferably have a particle size of 0.01 μm to 10 μm, more preferably 0.1 μm to 8 μm, most preferably 0.1 μm to 5 μm. The particle size is expressed as D50 of the particles. This means that 50% by weight of the particles have a size falling within the above range.

[0084] Fillers may be of natural or synthetic, mineral or non-mineral origin, provided that the fillers have sufficient heat resistance to maintain their solid physical structure at least during the molding process. Suitable fillers may include clays, nanoclays, carbon black, wood flour with or without oil, various forms of silica (precipitated or hydrated, gas phase or pyrolyzed, glassy, ​​molten or colloidal, including conventional sand), glass, metals, inorganic oxides (such as oxides of metals in periods 2, 3, 4, 5 and 6 of groups Ib, Iib, IIia, IIIb, IVa, IVb (except carbon), Va, Via, Vila and VIII of the periodic table), metal oxides (such as aluminum oxide, titanium oxide, zirconium oxide, titanium dioxide, nano-titanium oxide, aluminum hydroxide, vanadium oxide and magnesium oxide), aluminum or ammonium or magnesium hydroxide. Oxides, alkali or alkaline earth carbonates (such as calcium carbonate, barium carbonate, and magnesium carbonate), antimony trioxide, calcium silicate, diatomaceous earth, fuller's earth, diatomaceous earth, mica, talc, slate powder, volcanic ash, cotton dust, asbestos, kaolin, alkali and alkaline earth sulfates (such as barium sulfate and calcium sulfate), titanium, zeolite, wollastonite, titanium boride, zinc borate, tungsten carbide, ferrite, molybdenum disulfide, asbestos, cristobalite, aluminosilicates including vermiculite, bentonite, montmorillonite, Na-montmorillonite, Ca-montmorillonite, hydrated sodium calcium aluminum magnesium silicate hydroxide, pyrophyllite, magnesium aluminum silicate, lithium aluminum silicate, zirconium silicate, and combinations comprising at least one of the foregoing fillers. Suitable fiber fillers include glass fibers, basalt fibers, aramid fibers, carbon fibers, carbon nanofibers, carbon nanotubes, carbon buckyballs, ultra-high molecular weight polyethylene fibers, melamine fibers, polyamide fibers, cellulose fibers, metal fibers, potassium titanate whiskers, and aluminum borate whiskers.

[0085] Among these, calcium carbonate, talc, glass fiber, carbon fiber, magnesium carbonate, mica, silicon carbide, kaolin, wollastonite, calcium sulfate, barium sulfate, titanium, silicon dioxide, carbon black, ammonium hydroxide, magnesium hydroxide, aluminum hydroxide, and a combination comprising at least one of the foregoing substances are preferred. More preferably, the filler is selected from talc or glass fiber (except the fibers in the core of the pellet).

[0086] Optionally, the filler may be surface modified (eg treated) in order to improve the compatibility of the filler and the thermoplastic polymer, which promotes deagglomeration and uniform distribution of the filler in the polymer.Surface modification of fillers is known to the skilled person.

[0087] In the process according to the invention, the pellets preferably contain 1 wt.% to 40 wt.% of filler based on the total weight of the pellets. The amount of filler is at least 1 wt.%, preferably at least 2 wt.%, more preferably at least 4 wt.%. The amount of filler is at most 40 wt.%, preferably at most 35 wt.% and more preferably at most 30 wt.%.

[0088] Polymers for polymer jackets

[0089] The polymer sheath is made of a thermoplastic polymer and comprises a plurality of filler particles. The polymer sheath may also comprise one or more additives. In an embodiment, the polymer sheath is composed of at least one thermoplastic polymer, a plurality of filler particles and optionally one or more additives. The polymer of the sheath is preferably a thermoplastic polymer, more preferably a polypropylene homopolymer or copolymer. The thermoplastic polymer may be a single grade of polypropylene, but may also be a mixture of at least two different polypropylene grades.

[0090] The sheath may further contain one or more common additives, such as stabilizers, processing aids, impact modifiers, flame retardants, acid traps, inorganic fillers, colorants or components that further enhance the properties of the fiber-reinforced article, such as compounds that enhance interfacial bonding between the polymer and the filaments. It is preferred that the thermoplastic polymer of the sheath comprises one or more functionalized polyolefins, such as maleated polypropylene. The amount of the functionalized polyolefin added is dependent on the reinforced article and is typically 0.1 wt.% to 4 wt.%, preferably 0.2 wt.% to 3 wt.%, relative to the weight of the fibers in the multifilament.

[0091] The amount of thermoplastic polymer in the sheath of the pellets is preferably 15 wt.%-94.5 wt.%, more preferably 20 wt.%-90 wt.%, more preferably 25 wt.%-80 wt.%, more preferably 30 wt.%-70 wt.%, based on the total weight of the pellets.

[0092] The pellets according to the invention can be used to prepare reinforced articles. Reinforced articles are prepared using the molding composition. The molding composition can be provided by the pellets according to the invention alone or can be obtained, for example, by mixing the pellets with one or more (non-reinforcing) fillers as separate components. Alternatively, the molding composition can be provided by providing a composition pellet according to the invention comprising several fillers in a polymer sheath.

[0093] Fillers can be added at different stages of the process. Fillers can be added to the material itself during the production process or fillers can be added to the material in the form of a masterbatch during the production process. Fillers can also be added separately from the pellets during injection molding.

[0094] The molding step may involve the following steps: ia) providing a pellet of the present invention, wherein a filler may be present; or ib) mixing the pellet of the present invention and a filler to provide a molding composition; and ii) heating the molding composition to a high temperature. In this case, the filler itself may be added to the molding composition or the filler may be added in the form of a masterbatch containing a polymer and a filler. This masterbatch of fillers may contain fillers and polymers of various types and amounts. A mixture of several fillers and / or polymers may be present in the masterbatch. The masterbatch may be provided to the processing in the form of a pellet. The polymer used for the masterbatch may be polypropylene, such as a propylene homopolymer, a random copolymer, or a so-called multiphase copolymer of propylene and ethylene and / or another alpha-olefin. Most preferably, the thermoplastic polymer is a polypropylene homopolymer or copolymer. The thermoplastic polymer such as in the sheath of the pellet and the polymer in the masterbatch are preferably of the same type.

[0095] The mixing of the pellets and the filler can be carried out in a commonly used mixing device to provide a molding composition in which the pellets and the filler are evenly distributed. Commonly used mixing devices are blenders, such as V-blenders, ribbon blenders or cone blenders; mixers, such as jet mixers, planetary mixers or Banbury mixers; or extruders. The molding composition can be heated before, during and / or after the mixing of the molding composition. The polymer in the molding composition is melted and forms a matrix to be reinforced by the fibers.

[0096] Molding is carried out at a high temperature, which is a temperature where the molding composition has sufficient fluidity for molding (i.e., the polymer in the composition is melted). The high temperature is higher than the melting point of the thermoplastic polymer present in the sheath of the pellets. In the case where a masterbatch containing a filler and a polymer is used, the high temperature is also higher than the melting temperature of the polymer present in the masterbatch. The high temperature can be appropriately selected by the technician. Typically, the high temperature can be, for example, 150°C-500°C, 180°C-400°C or 200°C-300°C. In the case where the thermoplastic polymer in the pellets is a propylene homopolymer or copolymer, the high temperature is preferably 200°C-300°C.

[0097] Suitable examples of molding processes include injection molding, compression molding, extrusion and extrusion-compression molding. Injection molding is widely used to produce articles, such as automotive exterior parts (like bumpers), automotive interior parts (like dashboards), or automotive parts under the hood. Extrusion is widely used to produce articles, such as rods, sheets and tubes. Preferably, molding involves injection molding in the method according to the present invention. Reinforced articles are manufactured using the method according to the present invention. Preferably, the articles are automotive parts. It is very important that the present invention allows weight reduction of automotive parts with the same stiffness, because the automotive industry is always trying to reduce the weight of the car. The reinforced article according to the present invention can be, for example, a tailgate.

[0098] The thickness of the sheath of the pellet may vary around the circumference of the pellet; preferably, the thickness around the circumference of the pellet varies by up to 200% of the maximum thickness, depending on the flatness of the pellet; the flatter the pellet, the greater the variation in thickness. The thickness - meaning the maximum thickness around the pellet - is preferably at least 0.1 mm, more preferably at least 0.2 mm, most preferably at least 0.3 mm. The thickness of the sheath of the thermoplastic polymer is preferably at most 2 mm, more preferably at most 1.5 mm, most preferably at most 1 mm. The thickness of the sheath is largely determined by the size of the glass multifilaments and the amount of fibers desired in the pellet.

[0099] The length of the pellets is preferably between 10 mm and 50 mm, more preferably between 10 mm and 25 mm, most preferably between 10 mm and 20 mm. Preferably, the variation in the length of the pellets is between -10% and +10% based on the average length of a batch of pellets. When the length of the pellets is disclosed in this specification, the average length is meant unless otherwise stated.

[0100] It is further noted that the present invention relates to all possible combinations of features described herein, with particular preference given to those combinations of features present in the claims. It should also be understood that a description of a product comprising certain components also discloses a product consisting of these components. Similarly, it should also be understood that a description of a method comprising certain steps also discloses a method consisting of these steps. The present invention will now be illustrated by the following examples, but is not limited thereto.

[0101] Glass bubbles according to the present invention may include a surface coating. The coating may be bonded to the surface of the bubble or chemically react with the surface to modify or functionalize the surface. For example, a bifunctional silane-based coupling agent may be applied to the surface of the glass bubble. One end of the silane-based molecule will bond to the glass bubble; the other end of the molecule may bond to or combine with a polymer. Such chemical bridges provide improved physical properties of the material - especially tensile, elongation and stiffness properties.

[0102] Terms:

[0103] The following clauses provide aspects and embodiments of the invention.

[0104] 1. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0105] * the core comprises a plurality of filaments, preferably glass filaments, extending in the axial direction;

[0106] * said polymer sheath is at least substantially free of said filaments;

[0107] * the polymer sheath comprises a plurality of filler particles;

[0108] * The pellets comprise at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of filaments based on the total weight of the pellets.

[0109] 2. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0110] * the core comprises a plurality of filaments, preferably glass filaments, extending in the axial direction;

[0111] * said polymer sheath is at least substantially free of said filaments;

[0112] * the polymer sheath comprises a plurality of reinforcing filler particles;

[0113] * The pellets comprise at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of filaments based on the total weight of the pellets.

[0114] 3. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0115] * the core comprises a plurality of filaments, preferably glass filaments, extending in the axial direction;

[0116] * said polymer sheath is at least substantially free of said filaments;

[0117] * the polymer sheath comprises a plurality of lightweight filler particles;

[0118] * The pellets comprise at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of filaments based on the total weight of the pellets.

[0119] 4. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0120] * the core comprises a plurality of glass filaments extending in an axial direction;

[0121] * the polymer sheath comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0;

[0122] * The pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets.

[0123] 5. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0124] * the core comprises a plurality of glass filaments extending in an axial direction;

[0125] * the polymer sheath comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.% based on the total weight of the pellets;

[0126] * The pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets.

[0127] 6. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0128] * the core comprises from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter from 15 to 25 microns;

[0129] * the polymer sheath comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.% based on the total weight of the pellets;

[0130] * The pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets.

[0131] 7. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0132] * the core comprises from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter from 15 to 25 microns;

[0133] * the polymer sheath comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles in a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.%, based on the total weight of the pellets; the polymer sheath is a polypropylene homopolymer having a melt flow index (MFI) in the range of 40 g / 10 min to 80 g / 10 min;

[0134] * The pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets.

[0135] 8. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0136] * the core has a radius between 800 and 4000 micrometers and contains from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter of 15 to 25 micrometers;

[0137] * the polymer sheath has a thickness between 500 and 1500 microns and contains less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath contains a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.% based on the total weight of the pellets; the polymer sheath is a polypropylene homopolymer having a melt flow index (MFI) in the range of 40 g / 10 min to 80 g / 10 min;

[0138] * The pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets.

[0139] 9. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0140] * the core has a radius between 800 and 4000 micrometers and contains from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter of 15 to 25 micrometers;

[0141] * the polymer sheath has a thickness between 500 and 1500 microns and contains less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath contains a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.% based on the total weight of the pellets; the polymer sheath is a polypropylene homopolymer having a melt flow index (MFI) in the range of 40 g / 10 min to 80 g / 10 min;

[0142] * the pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets;

[0143] * wherein the core constitutes between 35% and 60% of the cross-sectional area of ​​the pellet and wherein the sheath constitutes between 40% and 65% of the cross-sectional area of ​​the pellet.

[0144] 10. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0145] * the core has a radius between 800 and 4000 micrometers and contains from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter of 15 to 25 micrometers;

[0146] * the polymer sheath has a thickness between 500 and 1500 microns and comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles (with up to 23% of the glass bubbles broken and having an average diameter between 15 and 25 microns) and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.%, based on the total weight of the pellets; the polymer sheath is a polypropylene homopolymer having a melt flow index (MFI) in the range of 40 g / 10 min to 80 g / 10 min and the amount of polymer in the pellets is between 40 wt.% and 80 wt.% of the total weight of the pellets;

[0147] * the pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets;

[0148] * wherein the core constitutes between 35% and 60% of the cross-sectional area of ​​the pellet and wherein the sheath constitutes between 40% and 65% of the cross-sectional area of ​​the pellet.

[0149] 11. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0150] * the core comprises a plurality of glass filaments extending in an axial direction;

[0151] * the polymer sheath comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0;

[0152] * the pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets;

[0153] * Wherein the exposure ratio (the number of filaments observed on the cut edge of the pellet divided by the total number of filaments multiplied by 100%) is at least 95%.

[0154] 12. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein:

[0155] * the core has a radius between 800 and 4000 micrometers and contains from 2000 to 5000 glass filaments extending in an axial direction, wherein the filaments have a diameter of 15 to 25 micrometers;

[0156] * the polymer sheath has a thickness between 500 and 1500 microns and comprises less than 5 wt.%, preferably less than 2 wt.% of the filaments based on the total weight of the polymer sheath; and the polymer sheath comprises a plurality of filler particles, the plurality of filler particles being a combination of glass bubbles (with up to 23% of the glass bubbles broken and having an average diameter between 15 and 25 microns) and nanoclay particles at a ratio of glass bubbles to nanoclay particles between 0.5 and 2.0; wherein the amount of filler particles is between 5 wt.% and 10 wt.%, based on the total weight of the pellets; the polymer sheath is a polypropylene homopolymer having a melt flow index (MFI) in the range of 40 g / 10 min to 80 g / 10 min and the amount of polymer in the pellets is between 40 wt.% and 80 wt.% of the total weight of the pellets;

[0157] * the pellets contain at least 40 wt.% and at most 50 wt.% of filaments based on the total weight of the pellets;

[0158] * wherein the core constitutes between 35% and 60% of the cross-sectional area of ​​the pellet and wherein the sheath constitutes between 40% and 65% of the cross-sectional area of ​​the pellet;

[0159] * Wherein the exposure ratio (the number of filaments observed on the cut edge of the pellet divided by the total number of filaments multiplied by 100%) is at least 95%.

[0160] Examples

[0161] Material:

[0162] As polyolefin, homopropylene with an MFR of 47 g / 10 min @ 230 C / 2.16 kg was used. As filaments, glass rovings with a diameter of 19 μm and 3000 tex (Advantex SE4220 produced by 3B) impregnated with an impregnation composition (size) were used. As fillers, glass bubbles with an average diameter of 16 or 30 μm without a surface coating (e.g. iM16k or iM30k from 3M) with a diameter of 210 μm were used. 2 Surface area of ​​0.45 g / cm 3 Density (for iM16K) and 0.6g / cm 3 Density (for iM30K) (measured according to ASTM D792-13). Or nanoclays (Adins NC (non-silane modified) and Adins 80T (silane modified) from Tolsa), the Adins 80T is a nanoclay with a density of 2 g / cm 3The specific gravity (ISO 787-10:1993) is 0.13 g / cm 3 Density (NET 005-03), with 210m 2 / g surface area (BET) (NET-069-03; ASTM D3663-84), (silane-modified) sepiolite clay with a d90 of 24 microns and a d50 of 7 microns and >99.9% of the particles have a diameter less than or equal to 45 microns. As additives, the following items are added: (UV) stabilizer (Irganox B225), coupling agent (ExxelorPO1020) and impregnating agent / low Mw hydrocarbon wax (Parafflex 4843A).

[0163] Test Method

[0164] The samples for testing were prepared using injection molding. The pellets were made according to the method disclosed in WO 2009 / 080281, where a premix containing a second filler was used as the polyolefin sheath. The premix was prepared using conventional mixing and extrusion. The samples for production testing were prepared using injection molding.

[0165] Tensile Tests Tensile modulus and tensile strength were tested according to ISO 527-2 (1A) (2012) at 23°C, 80°C and 120°C. Elongation at break was tested according to ISO 527-2 (1A) (2012) at 23°C. Tensile bars with dimensions of 150*10*4 mm were produced by injection molding according to ISO 527-2 (1A) (2012). Prior to testing, the samples were conditioned at 23±1°C and at a relative humidity of 50±5% for 7 days.

[0166] Isotropic modulus or tensile modulus: Isotropic modulus is tested according to tensile ISO 527-2 (1B) (2012) at 23°C. The isotropic substrate has dimensions of 270*310*3 mm, where 3 samples with dimensions of 150*10*4 mm were sheared at 0°, 45° and 90° in the flow direction during injection molding. Prior to testing, the samples were conditioned at 23±1°C and at a relative humidity of 50±5% for 7 days.

[0167] Density: Density is measured according to ISO 1183:1-2012 (method A) at 23°C and samples are conditioned at 23±1°C and 50±5% relative humidity for 7 days before testing.

[0168] Dart impact (FDI) / breaking force: FDI is tested according to ISO 6603-2:2000 at 23°C and -30°C. The sample size is 65*65*3mm and the dart diameter and weight are 20mm and 20kg respectively. Prior to testing, the samples are conditioned at 23±1°C and at a relative humidity of 50±5% for 7 days.

[0169] Charpy Impact Strength: Impact strength was tested according to ISO 179: 1-2010 at 23°C and -30°C. The sample size was 80*10*4 mm and the sample was conditioned at 23±1°C and at 50±5% relative humidity for 72 hours before testing. Due to the small size of the test strips, the fibers are most likely unidirectional. Both notched and unnotched tests were performed.

[0170] Fiber length: The fiber length of the filaments in the reinforced article is measured according to a custom STAMAXTAT test on injection molded 6*6*3 mm samples and calcined at T=600°C. After injection molding, the amount of glass breakage is determined as the average number (Ln) and the average weight (Lw). This number should be kept as high as possible, a decrease will result in a decrease in modulus.

[0171] Bubble rupture: Bubble rupture is calculated according to the following formula:

[0172]

[0173] ρ m = matrix density

[0174] ρ B =Glass bubble density

[0175] w m = matrix weight fraction

[0176] w R = Foam weight fraction (ash content)

[0177] ρ c = measured matrix density

[0178] Wherein the parameters are determined by density measured using the ASTM D792-13 method, the weight fraction of bubbles is measured by ash content measurement (ASTM D2584-11).

[0179] Comparison A

[0180] A first comparative pellet A was used that contained 40.00% (40%) of glass fiber filaments forming a core and further contained a polymer sheath containing 54.03% homopropylene, based on the total weight of the pellet. The composition lacked filler. The polymer sheath further contained 0.45% stabilizer, 2.00% coupling agent, and 3.52% wax, based on the total weight of the pellet. The density of the pellet was measured to be 1.22 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 4850 MPa and 3.97 (m / s) respectively. 2 The isotropic tensile strength was determined to be 64.3 MPa. The Charpy impact strength at 23°C and -30°C was tested for both notched and unnotched conditions; the impact strength at 23°C and -30°C for notched conditions was 20.32 KJ / m 2 and 27.76KJ / m 2 And the values ​​without notch are 49.43KJ / m at 23℃ and -30℃ respectively. 2 and 49.5KJ / m 2 The FDI breaking force was determined to be 2245 N and 2184 N at 23° C. and −30° C., respectively. The glass fiber filaments in the object had an Lw fiber length of 2.38 mm.

[0181] Contrast B

[0182] A second comparative pellet B was used that contained 50.00% (50%) of glass fiber filaments forming a core and further contained a polymer sheath containing 42.74% homopropylene, based on the total weight of the pellet. The composition lacked filler. The polymer sheath further contained 0.36% stabilizer, 2.50% coupling agent, and 4.40% wax, based on the total weight of the pellet. The density of the pellet was measured to be 1.32 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 6040Mpa and 4.56(m / s) respectively. 2 The isotropic tensile strength was determined to be 67.8 MPa. The FDI breaking force was determined to be 2292 N and 2525 N at 23°C and -30°C, respectively. In the formed article, the Lw fiber length was 2.08 mm.

[0183] Example 1

[0184] A first pellet according to the present invention was used which contained 36.00% (36%) of glass fibers forming a core and further contained a polymer sheath (containing 50.20% homopolypropylene, 8.00% iM16k glass bubbles as a filler, further containing 0.43% stabilizer, 2.20% coupling agent, 3.17% wax), based on the total weight of the pellet. The density of the pellet according to Example 1 was measured to be 1.11 g / cm3 The isotropic modulus and effective isotropic modulus were determined to be 4400 MPa and 3.96 (m / s) respectively. 2 The isotropic tensile strength was determined to be 68.0 MPa. The percentage of bubble rupture as determined by the above formula was higher than 22.5%. The Charpy impact strength at 23°C and -30°C was tested for both notched and unnotched cases. The impact strength at 23°C and -30°C in the notched case was 22.5 KJ / m 2 and 27.0KJ / m 2 The values ​​without notch are 57.7KJ / m at 23℃ and -30℃ respectively. 2 and 45.8KJ / m 2 The FDI breaking force was determined to be 2110 N and 2304 N at 23° C. and −30° C., respectively. The average number of white spots was determined to be 10.9; which was less than 14.7 of Comparative A above. In the object, the Lw fiber length was 2.10 mm.

[0185] Example 2

[0186] A second pellet according to the present invention was used comprising 40.00% (40%) of glass fibers forming a core and having a polymer sheath (comprising 48.86% polyolefin, 5.00% filler in the form of nanoclay Adins 80T (described above), further containing 0.37% stabilizer, 2.25% coupling agent, and 3.52% wax), based on the total weight of the pellet. The density of the pellet of Example 2 was measured to be 1.28 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 5768 MPa and 4.51 (m / s) respectively. 2 The isotropic tensile strength was determined to be 70.4 MPa. The Charpy impact strength was tested at both 23°C and -30°C for both notched and unnotched conditions. The impact strength at 23°C and -30°C for notched conditions was 18.6 KJ / m 2 and 22.1KJ / m 2 The values ​​without notch are 61.7KJ / m at 23℃ and -30℃ respectively. 2 and 52.3KJ / m 2。 The FDI breaking force was determined to be 2098 N and 2170 N at 23° C. and −30° C., respectively. In the object, the Lw fiber length was 2.10 mm.

[0187] Example 3

[0188] A third pellet according to the present invention was used, based on the total weight of the pellet, of 50.00% (50%) of glass fiber as a core and further comprising a polymer sheath (comprising 37.42% homopropylene, 5.10% of a filler in the form of iM16K glass bubbles, further containing 0.33% of a stabilizer, 2.75% of a coupling agent, and 4.40% of a wax). The density of the pellet of Example 3 was measured to be 1.28 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 6190 MPa and 4.84 (m / s) respectively. 2 The isotropic tensile strength was determined to be 57.8 MPa. The percentage of bubble rupture as determined by the above formula was higher than 20%. The FDI breaking force was determined to be 2228 N and 2254 N at 23° C. and -30° C., respectively. In the object, the fiber length was 2.17 mm.

[0189] Example 4

[0190] A fourth pellet according to the present invention was used, comprising 50.00% (50%) of glass fiber as a core and further comprising a polymer sheath (comprising 35.64% homopropylene, 6.80% of a filler in the form of iMK16k glass bubbles, further containing 0.32% of a stabilizer, 2.84% of a coupling agent, and 4.40% of a wax), based on the total weight of the pellet. The density of the pellet of Example 4 was measured to be 1.25 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 6335 MPa and 5.10 (m / s) respectively. 2 The isotropic tensile strength was determined to be 62.2 MPa. The percentage of bubble rupture as determined by the above formula was higher than 17.5%. The FDI breaking force was determined at the above temperatures and was measured to be 2164 N and 2269 N at 23°C and -30°C, respectively. In the object, the Lw fiber length was 2.08 mm.

[0191] Example 5

[0192] A fifth pellet according to the present invention was used, based on the total weight of the pellet, of 40.00% (40%) glass fibers and further comprising a polymer sheath (comprising 44.4% homopropylene, 4.00% filler in the form of iM16K glass bubbles, 5.00% second filler in the form of nanoclay AdinsNC (described above), further containing 0.33% stabilizer, 2.75% coupling agent, 3.52% wax). The density of the pellet of Example 5 was measured to be 1.22 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 6000Mpa and 4.92(m / s) respectively. 2The isotropic tensile strength was determined to be 57.8 MPa. The percentage of bubble rupture as determined by the above formula was higher than 20%. The FDI breaking force was determined to be 2228 N and 2254 N at 23°C and -30°C, respectively.

[0193] Example 6

[0194] A sixth pellet according to the present invention was used that contained 45.00% (45%) glass fibers and further contained a polymer sheath (comprising 41.92% homopropylene, 6.00% filler in the form of iM16K glass bubbles, further containing 0.33% stabilizer, 2.75% coupling agent, 4% wax) based on the total weight of the pellet. The density of the pellet of Example 6 was determined to be 1.20 g / cm 3 The isotropic modulus and effective isotropic modulus were determined to be 6000 MPa and 4.98 (m / s) respectively. 2 The isotropic tensile strength was determined to be 58.6 MPa. The percentage of bubble collapse as determined by the above formula was less than 10%. The FDI breaking force was determined to be 1901 N at 23°C. Table 1 below summarizes the composition of the pellets according to the invention and the comparative pellets. Table 2 below summarizes the characteristics of these pellets.

[0195] Table 1: Composition of pellets (% in wt. % based on the total weight of the pellets)

[0196]

[0197] Table 2: Characteristics of pellets

[0198]

[0199] Undetermined = Undetermined

[0200] There is a significant effect of adding fillers (Example 3 compared to Comparative Example B) on density, which is reduced. There is no significant effect of adding fillers (Examples 1-4 compared to Comparative Examples A and B) on Charpy (non-) notched impact strength. It is observed that the FDI force-to-break values ​​for the examples using glass bubbles are somewhat lower. This may be due to the presence of significantly more glass and this may result in slightly more glass breakage, although this is minimized by using high-strength glass bubbles. With the use of fillers according to the invention, significant improvements were observed in the isotropic modulus test (Comparative B compared to Examples 3 and 4 and Comparative A compared to Example 2). The same is true for the effective isotropic modulus (which is the ratio of isotropic modulus to density), which is significantly increased.

[0201] By adjusting the amount of glass filaments and the amount of filler, the characteristics can be adjusted. When comparing Example 1 (36% glass filaments / 8% glass bubbles) with Example 6 (45% glass filaments / 6% glass bubbles), it can be observed that the density increases to some extent from 1.11 to 1.20 and the isotropic modulus increases dramatically from 4400 MPA to 6000 MPA.

Claims

1. A pellet having an axial direction; said pellet comprising a core extending in said axial direction and comprising a polymer sheath having been applied around said core, wherein: * the core comprises a plurality of filaments, preferably glass filaments, extending in the axial direction; * said polymer sheath is at least substantially free of said filaments, preferably said polymer sheath comprises less than 5 wt.% of said filaments based on the total weight of said polymer sheath; *the polymer sheath comprises a plurality of filler particles; wherein the filler particles are glass bubbles, nanoclay particles, or a combination thereof, * The pellets comprise at least 30%, preferably at least 35%, more preferably at least 40%, and preferably at most 60%, preferably at most 50% by weight of filaments based on the total weight of the pellets.

2. The pellet according to claim 1, wherein The filler particles are a combination of glass bubbles and nanoclay particles, more preferably in a ratio of glass bubbles to nanoclay particles between 0.5 and 2.

0.

3. A granulate according to any one of the preceding claims, wherein The pellets contain between 3 wt.% and 20 wt.%, preferably between 5 wt.% and 10 wt.% of the filler particles, based on the total weight of the pellets.

4. A granulate according to any one of the preceding claims, wherein The core comprises from 2000 to 5000 filaments and / or wherein the filaments have a diameter of from 5 to 50 microns, more preferably from 10 to 30 microns and most preferably from 15 to 25 microns.

5. A granulate according to any one of the preceding claims, wherein The polymer sheath is a polyolefin, preferably polypropylene, more preferably a polypropylene homopolymer, more preferably having a melt flow index (MFI) of at least 20 g / 10 min and / or having an MFI of up to 150 g / 10 min, most preferably in the range of 40 to 80 g / 10 min.

6. A granulate according to any one of the preceding claims, wherein The radius of the core is between 800 and 4000 microns and / or wherein the thickness of the polymer sheath is between 500 and 1500 microns.

7. A granulate according to any one of the preceding claims, wherein The core constitutes between 35% and 60% of the cross-sectional area of ​​the pellet and wherein the sheath constitutes between 40% and 65% of the cross-sectional area of ​​the pellet.

8. A granulate according to any one of the preceding claims, wherein The polymeric sheath is substantially free of filaments, which means that it comprises less than 2 wt. % of filaments based on the total weight of the polymeric sheath.

9. A granulate according to any one of the preceding claims, wherein The filler particles are glass bubbles and wherein the glass bubbles are fractured by at most 30%, preferably at most 23%.

10. A granulate according to any one of the preceding claims, wherein The filler particles are glass bubbles and wherein the glass bubbles have an average diameter of between 10 and 30 microns, preferably between 15 and 25 microns.

11. A granulate according to any one of the preceding claims, wherein The amount of polymer in the pellets is between 40 wt.% and 80 wt.% based on the total weight of the pellets.

12. A pellet according to any one of the preceding claims, wherein The exposed ratio, which is the number of filaments observed on the cut edge of the pellet divided by the total number of filaments multiplied by 100%, is at least 95%.

13. A reinforced article obtained by molding a plurality of said granules according to any one of claims 1 to 12, preferably wherein said reinforced article is an automotive part, more preferably a tail panel and / or preferably wherein said article is obtained by injection molding a plurality of said granules.

14. The reinforced article according to claim 13, wherein: The article, preferably the automotive article, more preferably the tailgate has an isotropic modulus of at least 5000 MPA, preferably at least 5500 MPA, more preferably at least 6000 MPA and / or a modulus of at least 3.5 (m / s) 2 and 7(m / s) 2 Between, preferably 4 (m / s) 2 Up to 6 (m / s) 2 , more preferably 4.5 (m / s) 2 Up to 5.5 (m / s) 2 An effective isotropic modulus and / or a density of at most 1.3 (g / cm3), preferably 1.28 (g / cm3), more preferably 1.25 (g / cm3).

15. A method for making pellets, the method comprising the following steps: i) unwinding a plurality of continuous filaments, preferably glass filaments, from a packaging; ii) optionally, applying an impregnation composition to the plurality of filaments to form an impregnated plurality of filaments; iii) providing a polymer composition comprising at least one polymer and a plurality of filler particles, wherein the filler particles are glass bubbles, nanoclay particles, or a combination thereof, iv) applying a polymer sheath comprising filler particles around the impregnated plurality of continuous filaments, preferably by a wire coating process, to form a sheathed bundle comprising a core comprising the plurality of filaments and comprising a sheath comprising the polymer and filler particles: and v) cutting the jacketed bundle into individual pellets comprising a core extending in an axial direction and comprising a polymer jacket having been applied around the core, wherein: * the core comprises a plurality of filaments extending in an axial direction; * the pellets contain at least 30%, preferably at least 35%, and at most 40%, preferably at most 60%, most preferably at most 50% by weight of filaments based on the total weight of the pellets; * the polymer sheath is at least substantially free of filaments; *The polymer sheath comprises a plurality of filler particles.

Citation Information

Patent Citations

  • Chemically treated glass fibers for reinforcing polymeric materials and processes

    EP0206189A1

  • Binder for glass fiber, glass fiber for olefin resin reinforcement, and process for producing olefin resin composition for fiber-reinforced molding

    EP1460166A1

  • Aqueous sizing composition and sized glass fibers and method

    US4338233A

  • Fiber reinforced thermoplastic resin molded product having a good surface appearance

    US6291064B1

  • Process for producing long glass fibre-reinforced thermoplastic compositions

    WO2009080281A1